Assessment of the efficiency and performance of different PV system configurations under various fault conditions - Othman, Raghad Adeeb; Al-Yozbaky, Omar Sharaf Al-Deen Yehya (International Journal of Power Electronics and Drive Systems (IJPEDS), 2025)
Partial shadowing, bypass-diode issues, photovoltaic (PV) module deterioration, and wiring issues are examples of PV failures that have a substantial effect on power production and cause distinct peaks in a PV system's P-V curves. Various PV fault types have been used in the solar cell system in this work. Four types were used: open circuit, line to ground, cross-line to line, and intra-line to line. The impact of various PV system failure types on the system's performance was emphasized in this study. MATLAB is used to display the simulation results for the four approaches (series parallel (SP), total cross tied (TCT), honeycomb (HC), and bridge link (BL)) under various fault scenarios. The current-voltage (I-V) and power-voltage (P-V) curves are used to compare the results for each fault scenario. The open circuit fault between PV (7.8) in the first string and PV (18.19) in the fourth string resulted in a 40% decrease in the short-circuit current of the photovoltaic system compared to its normal value in the SP topology, while in the HC and BL topologies, the current value exceeded the allowable limit. This, in turn, had an impact on the (I-V) characteristics of this topology. The fault's impact was minimal and within the typical bounds of its (I-V) characteristics in the TCT topology.